Clinical practice guidelines. Advantages and disadvantages. - Alfredo Darío Espinosa Brito; Luis Gustavo Del Sol Padrón; Alfredo Alberto Espinosa Roca; José Luis Garriga Valdés; Brandy Viera Valdés (Medisur)
The elaboration and implementation of clinical practice guidelines has been a novel element, which has been introduced into medical care in health facilities over the last few years. Our country has not been the exception, and especially our Hospital Dr. Gustavo Aldereguía Lima, adds up to more than a decade with the employment of these tools. In this paper, the advantages and disadvantages of using guidelines are assessed, according to our own point of view and starting from the referred practice. Better informed patients, health systems who see to keep control of sanitary expenditures and a growing professional competence, are very efficient factors that will keep a process of improvement and efficiency in motion, which will inevitably lead to an objective assessment of the services we provide to patients, mainly for the sake of the ill and the professionals.